2014
DOI: 10.3389/fphys.2014.00075
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor associated macrophages in tumor angiogenesis and lymphangiogenesis

Abstract: Tumor angiogenesis is an essential process for supplying rapidly growing malignant tissues with essential nutrients and oxygen. An angiogenic switch allows tumor cells to survive and grow, and provides them access to vasculature resulting in metastatic disease. Monocyte-derived macrophages recruited and reprogrammed by tumor cells serve as a major source of angiogenic factors boosting the angiogenic switch. Tumor endothelium releases angiopoietin-2 and further facilitates recruitment of TIE2 receptor expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
384
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(412 citation statements)
references
References 154 publications
10
384
0
18
Order By: Relevance
“…These soluble stimuli include IL-8, IL-10, adrenomedullin (ADM), TNF-a, TGF-b, VEGFs, uPA, colony stimulating factor 1 (CSF-1), and chemokine (C-C motif) ligand 2 (CCL2). 21,22,44 In the present study, we proved that LPS facilitates pancreatic cancer cell invasion, while MCM promotes both pancreatic cancer cell growth and invasion. Both LPS and MCM repressed PP2Ac expression in pancreatic cancer cells in vitro, suggesting PP2Ac regulation could be involved in inflammation-driven pancreatic cancer progression.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These soluble stimuli include IL-8, IL-10, adrenomedullin (ADM), TNF-a, TGF-b, VEGFs, uPA, colony stimulating factor 1 (CSF-1), and chemokine (C-C motif) ligand 2 (CCL2). 21,22,44 In the present study, we proved that LPS facilitates pancreatic cancer cell invasion, while MCM promotes both pancreatic cancer cell growth and invasion. Both LPS and MCM repressed PP2Ac expression in pancreatic cancer cells in vitro, suggesting PP2Ac regulation could be involved in inflammation-driven pancreatic cancer progression.…”
Section: Discussionmentioning
confidence: 71%
“…Quality control of MCM was performed by evaluating secretion of the cytokines interleukin-8 (IL-8) and tumor necrosis factor-a (TNF-a) ( Figure 1C). 20,21,22 MCM promoted pancreatic cancer cell growth slightly ( Figure 1D) and stimulated invasion remarkably ( Figure 1E). These in vitro data suggest that inflammation could be a favorable factor for pancreatic cancer progression by accelerating cell growth and invasion.…”
Section: Inflammatory Stimuli Promotedpancreatic Cancer Cell Growth Amentioning
confidence: 99%
“…Classically activated M1 macrophages have been linked to protective role against the tumor, while M2 macrophages seem to have a tumour-supporting role [26]. Intriguingly, YKL-40 is acknowledged as a marker of alternatively activated M2 macrophages, which have been shown to suppress adaptive tumor-specific immune response and promote tumor growth, angiogenesis, invasion, metastasis and stroma remodeling [26,27]. Further, YKL-40 seems to be a pro-angiogenic factor itself as it has been shown to induce VEGF expression in U87 glioblastoma cells and angiogenesis in vitro and in vivo [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, YKL-40 is acknowledged as a marker of alternatively activated M2 macrophages, which have been shown to suppress adaptive tumor-specific immune response and promote tumor growth, angiogenesis, invasion, metastasis and stroma remodeling [26,27]. Further, YKL-40 seems to be a pro-angiogenic factor itself as it has been shown to induce VEGF expression in U87 glioblastoma cells and angiogenesis in vitro and in vivo [27][28][29]. In the study by Faibish et al blocking YKL-40 with monoclonal antibody was demonstrated to suppress tumor growth and angiogenesis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Макрофаги являются производными моноцитов, активируются хемокинами, секрети-руемыми многими опухолевыми клетками [67]. Хемокины инду-цируют продукцию макрофагами ангиогенных факторов, VEGF и ММР, разрушающих клеточный матрикс и способствующих миграции опухолевых и лимфоидных клеток [50,54,68,69]. Раз-личают М1 макрофаги, ассоциированные с острым воспалением и противоопухолевой активностью, и М2 макрофаги, связанные с опухолевой прогрессией [50,64,67,69,70].…”
Section: Cd25unclassified